Detection of CO(1−0) Emission at the Tips of the Tidal Tail in the Antennae Galaxies - Maeda, Fumiya; Egusa, Fumi; Tsujita, Akiyoshi; Inoue, Shuhei; Kohno, Kotaro; Komugi, Shinya; Ohta, Kouji; Asada, Yoshihisa; Fujimoto, Yusuke; Habe, Asao; Hatsukade, Bunyo; Inoue, Shin; et al. (The Astrophysical journal, 2024)
The tip of the tidal tail, resulting from an encounter between galaxies, features gas concentrations and some star-forming regions, such as tidal dwarf galaxies (TDGs). This region provides a unique laboratory for examining the star formation process in a dynamical environment distinct from that of disk galaxies. Using the Nobeyama 45 m telescope, we conducted 12 CO(1−0) position-switching observations at the tips of the southern tidal tail in the Antennae galaxies. We detected CO emission not only from the two star-forming TDG candidates but also in regions with no significant star formation. Adopting a Galactic CO-to-H 2 conversion factor without helium correction, the H 2 gas surface density is ∼5–12 M ⊙ pc −2 . In most regions, the molecular-to-atomic gas ratio is around unity (0.6–1.9), but we find a region with a high ratio with a 3 σ lower limit of >7.2. The star formation efficiency (SFE) of molecular gas is notably low (<0.15 Gyr −1 ), indicating less active star formation than in both nearby disk galaxies (∼0.5–1.0 Gyr −1 ) and other TDGs previously observed. Including previous observations, the molecular gas SFEs vary widely among TDGs/tidal tails, from 10 −2 to 10 Gyr −1 , demonstrating significant variations in star formation activity. Potential factors contributing to the low SFE in the Antennae tail tips include extensive tides and/or the young age of the tail.